FRI0344 Extra-Glandular Manifestations of Primary Sjögren Syndrome Excluded from Disease Activity Indexes. (15th July 2016) - Fernandez Castro, M.; Andreu, J.L.; Sanchez-Piedra, C.; Olive, A.; Rosas, J.; Martinez Taboada, V.
Abstract : Background: Primary Sjögren syndrome (pSS) is a systemic autoimmune disease characterized by lymphocyte infiltration of the exocrine glands. Nevertheless, it can affect any organ and develop extra-glandular manifestations that even can precede the typical glandular manifestations and delay the diagnosis. Objectives: The aim of our study was to evaluate the extra-glandular manifestations not included in disease activity indexes (Sjogren's Syndrome Disease Activity Index and EULAR Sjogren's Syndrome Disease Activity Index). Methods: We conducted a multicenter descriptive transversal study of pSS patients fulfilling European/American criteria, from 33 Spanish rheumatology departments. Patients were selected by randomization. Every patient was interviewed for data collection and signed an informed consent. Data were also collected by reviewing medical records. Local ethics committees approved the study. Variables were analysed by descriptive statistical methods, using means, medians and rates. Chi-square was used to establish the statistical associations. A p<0.05 was considered significant. Results: Four hundred and thirty-seven patients were included. Ninety-five percent of them were women. The median age of the cohort was 58 years. Nineteen percent of the patients referred involvement of the trachea or upper airway. Twenty-one percent of the patients developed Raynaud phenomenon. Twelve (2.7%) patients suffered cardiac impairment (6 pericarditis and 6 cardiac conduction disorders). Thirteen percent of the patients referred digestive involvement, being chronic atrophic gastritis the most frequent condition (21 patients), followed by esophageal motility alteration (12 patients), followed by lymphocytic colitis (3 patients). Seven percent of the patients developed hepatic involvement: primary biliary cirrhosis and autoimmune hepatitis were the most frequent (15 and 14 patients, respectively), followed by autoimmune cholangitis in 3 patients; 55 patients (13%) had anti-LKM antibodies, 15 patients anti-mitochondrial antibodies, and 5 patients anti-smooth muscle antibodies. Seven patients had pancreatic involvement. Seventy-eight patients (18%) had thyroid involvement: anti-thyroid peroxidase (anti-TPO) hypothyroidism was the most frequent (41 patients), followed by subclinical hypothyroidism in 23 patients, negative anti-TPO hypothyroidism in 12 patients, anti-TPO+ hyperthyroidism in one patient and anti-TPO- hyperthyroidism in one patient. Thyroid involvement was significantly more frequently in patients with anti-Ro+. Raynaud phenomenon was significantly more frequent in patients with anti-La antibodies. Digestive involvement was significantly more frequent in patients with low C3. Pancreatic involvement was significantly more frequent in patients with low C3 and C4. Hepatic and trachea involvement were significantly more frequent in patients with hypergammaglobulinemia. Conclusions: Twenty percent of the patients with primary Sjögren syndrome developed extra-glandular manifestations not included in disease activity indexes. Serological characteristics may be helpful in identifying this subgroup of patients. Disclosure of Interest: None declared